Clinical remission of psoriatic arthritis in patients receiving continuous biological therapies for 1 year: the experience of an outpatient dermatological clinic for psoriasis. (1st December 2014) - Graceffa, D.; Maiani, E.; Sperduti, I.; Ceralli, F.; Bonifati, C.
Summary Background The data in the literature concerning the frequency of remission of inflammatory arthritis in patients with psoriatic arthritis (PsA) are limited and conflicting. Aim To evaluate the frequency of clinical remission in inflammatory arthritis in a cohort of patients with PsA receiving continuous treatment (1 year) with tumour necrosis factor‐α inhibitors or ustekinumab, as well as the clinical covariates affecting remission. Methods We retrospectively evaluated 74 patients with PsA attending our psoriasis outpatient dermatology clinic. Remission of PsA was defined as documented absence of clinical signs related to arthritis (no tender or swollen joints), enthesitis or dactylitis. Patients were examined every 3 months for 1 year. Results At 1 year > 40% of patients had clinical remission of inflammatory arthritis. Predictors of remission were absence of fibromyalgia (FM) at baseline and having < 11 tender joints. Conclusions Clinical remission of inflammatory arthritis can be obtained in a significant proportion of patients by continuous treatment with biological drugs. A large number of tender joints and the presence of FM can make remission less likely.